Numerical modeling of single droplet flash boiling behavior of e-fuels considering internal and external vaporization. (15th January 2022) - Saha, Avijit; Grenga, Temistocle; Deshmukh, Abhishek Y.; Hinrichs, Jörn; Bode, Mathis; Pitsch, Heinz
Abstract: In recent years, significant efforts have been made to develop e-fuels from renewable electricity and carbon sources for enabling highly efficient and advanced propulsion systems. Compared to conventional fuels, such fuels can have very different thermo-physical properties depending on their molecular structure. Particularly, fuels with high vapor pressures are highly susceptible to flash boiling depending on boundary conditions, which can significantly alter the spray formation and mixing behavior. Thus, it becomes imperative to develop a fundamental understanding of the underlying physics associated with the flash boiling of these fuels in a single droplet configuration. In this work, oxymethylene ethers (OME x ) are chosen as a generic example to study the flashing behavior of newly developed e-fuels. This study employs the Lagrangian Particle Tracking (LPT) approach considering both internal and external vaporization of flash boiling single droplets. The internal vaporization model includes several sub-models that compute bubble number density, bubble growth rate, and droplet bursting criterion. External vaporization is modeled considering heat transfer from the droplet interior to the droplet surface and from the surrounding gas to the droplet surface. The study reveals that the formation and subsequent growth of vapor bubble nuclei is the primary source causing the transition of the metastable liquid phase into the stable state. We found that for moderate to high superheating degree, the bubble growth characteristics indicate three distinct growth phases: (1) surface tension-controlled, (2) transition, and (3) inertia-controlled, whereas, for low superheating degree, only two of these were present, namely (1) surface tension-controlled, and (2) transition phase. It is also observed that the chain length of OME x has significant impact on bubble dynamics. OME4 is found to have a larger critical nucleus, a longer time delay in bubble growth, and a slower growth rate compared with dimethyl ether (DME). Furthermore, a quantitative analysis shows that droplets burst earlier with increasing superheating degree. In addition, it is found that the system pressure has a negligible influence on the initiation of the bursting process, except when the superheating degree is very low. Highlights: A novel reduced order flash boiling model in an LPT framework is proposed. Relative importance of internal and external vaporization is assessed. Distinct bubble growth phases are captured for varying operating conditions. Internal vaporization is predicted as the primary source of phase transition.